How are self-rated health and diagnosed disease related to early or deferred retirement? A cross-sectional study of employees aged 55-64 - Kerstin Nilsson; Anna Rignell Hydbom; Lars Rylander (BMC, 2016)
Abstract Background More people will probably continue working into old age in the future due to the increased size of aging populations in many countries. We therefore need to know more about older workers' health in relation to their work situation and retirement. This study is a part of a theoretical development of older workers' situations. Older workers' situations are theoretically themed in nine areas by the authors of this study. The aims of the study were to investigate the relationship between: i) diagnosed disease and factors in older workers' situations, theoretically themed in nine areas; ii) self-rated health and factors in older workers' situations, theoretically themed in nine areas; iii) diagnosed disease and self-rated health; and iv) the relationships between these health measures and retirement. Methods A questionnaire-based cross-sectional study, using logistic regression, with 1,756 health care personnel aged 55-64 years. The questionnaire used gave an overview of most different areas in the older workers' situations. Result There was a difference in the participants' frequency of objectively specified diagnosed disease and their subjectively experienced self-rated health. A bad self-rated health was related higher to early retirement than diagnosed diseases. In the multivariate model, having 'Diagnosed disease' was not significantly related to whether older workers thought they could not work beyond 65 years of age. A bad 'Self-rated health' was also more highly related to whether older workers thought they could not work beyond 65 years, than if the respondents stated that a 'Diagnosed disease is a hindrance in my daily work' in the multivariate model. Conclusion This study showed an important difference between older workers' own experiences and the effect of their self-rated health and their diagnosed diseases. Subjective self-rated health seems to be more important to people's retirement planning than diagnosed disease. The most important factors affecting older workers' self-rated health was the degree to which they felt physically and mentally fatigued, their possibilities for revitalization, and issues of work satisfaction, age discrimination and attitudes of managers to them as seniors.